2014
DOI: 10.1039/c4py00773e
|View full text |Cite
|
Sign up to set email alerts
|

A base–conjugate-acid pair for living/controlled ring-opening polymerization of trimethylene carbonate through hydrogen-bonding bifunctional synergistic catalysis

Abstract: The ring-opening polymerization (ROP) of trimethylene carbonate (TMC) using a base-acid binary organocatalyst system of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD) and Brønsted acid trifluoromethanesulfonic acid (TFA) with benzyl alcohol (BnOH) as the initiator has been investigated. The MTBD and its conjugate-acid pair H-bonding bifunctional synergistic activation mechanism was demonstrated by NMR measurements, and the living/controlled nature of MTBD/TFA catalyzed ROP of TMC was confirmed by the kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Here, a synergistic catalytic mechanism was proposed, in which the bisurea activated the carbonyl group of monomer and MTBD facilitated the nucleophilic attack of the initiating/propagating alcohol by hydrogen bonding (Scheme ) . Kiesewetter expounded that (thio)urea/MTBD mediated ROP of VL proceeded through one of two mechanisms, (thio)‐imidate mechanism and classic H‐bond mediated mechanism.…”
Section: Resultsmentioning
confidence: 91%
“…Here, a synergistic catalytic mechanism was proposed, in which the bisurea activated the carbonyl group of monomer and MTBD facilitated the nucleophilic attack of the initiating/propagating alcohol by hydrogen bonding (Scheme ) . Kiesewetter expounded that (thio)urea/MTBD mediated ROP of VL proceeded through one of two mechanisms, (thio)‐imidate mechanism and classic H‐bond mediated mechanism.…”
Section: Resultsmentioning
confidence: 91%
“…To date, the squaramide‐mediated ROP of lactide was reported on one occasion using a squaramide/(−)‐sparteine two‐component catalytic mixture . While the present study was in progress, a Pt‐functionalized aminosquaramide was also reported to oligomerize lactide …”
Section: Introductionmentioning
confidence: 66%
“…Three strategies of 5 hydrogen-bonding activation existed in the ROP of cyclic carbonyl-containing monomers: (i) the simultaneous activation of an alcohol group and a carbonyl function by a unique bifunctional catalyst provided with a hydrogen bond donor and an acceptor, for example thiourea-amine catalysts were used to catalyze the ROP of lactide by Waymouth and Hedrick in 2005 [33]; (ii) the catalytic system consisted of two separate species with one of them acted as hydrogen bond 10 donor and the other as hydrogen bond acceptor, which was demonstrated by thiourea/amine [34][35][36]; (iii) the single activation of an alcohol group by a hydrogen bond acceptor, such as phosphazene [37,38]. In continuation of our interest in organocatalysis in ROPs [36, [39][40][41][42], we envisioned the concept of multicatalysis [43] should pioneer in an HBD cooperating with BA model in polymerizations. 15…”
Section: Accepted Manuscriptmentioning
confidence: 99%